2011
DOI: 10.2166/wh.2010.138
|View full text |Cite
|
Sign up to set email alerts
|

Pathogen destruction and solids decomposition in composting latrines: study of fundamental mechanisms and user operation in rural Panama

Abstract: The relationship between temperature, high pH, desiccation, decomposition, pathogen destruction, and user operation in active double vault urine diverting (DVUD) composting latrines located in the Bocas del Toro region of Panama was assessed. Latrine samples were analyzed for temperature, pH, % moisture, carbon-to-nitrogen (C/N) ratio, and presence of specific pathogens.Surveys and visual inspections were used to verify use and type of dry material desiccant added.Measurements supported findings that compost l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(60 citation statements)
references
References 7 publications
1
59
0
Order By: Relevance
“…This study confirms and further explains the results and conclusion of Mehl et al (2011) which also found that (1) compost latrines do not always reach the Safe Zone of Pathogen Destruction and (2) compost needed to be composted for more than 6 months due to the existence of pathogens and helminths. This study was performed on a single, typical latrine, with detailed temperature readings, while Mehl et al (2011) measured only one temperature value in multiple latrines.…”
Section: Resultssupporting
confidence: 86%
“…This study confirms and further explains the results and conclusion of Mehl et al (2011) which also found that (1) compost latrines do not always reach the Safe Zone of Pathogen Destruction and (2) compost needed to be composted for more than 6 months due to the existence of pathogens and helminths. This study was performed on a single, typical latrine, with detailed temperature readings, while Mehl et al (2011) measured only one temperature value in multiple latrines.…”
Section: Resultssupporting
confidence: 86%
“…We expect this method to be more applicable in tropical and sub-tropical regions where A. lumbricoides is prevalent and environmental conditions are favorable for ova development [12][13]. further research is needed to determine the usefulness of this method for determining ova viability in applications other than human fecal materials applied onto agricultural soils, such as sewage sludge treatment processes.…”
Section: Discussionmentioning
confidence: 99%
“…then, the spatula was used to till the top few cm of the soil surface to blend in the ova-biosolid mixture. additional deionized (di) water was added to the biosolid-amended soil to increase the moisture content of each microcosm to approximately 22.25% (less than 25% suggested for pathogen destruction) [12,34]. a total of 48 microcosms were prepared.…”
Section: Microcosm Preparationmentioning
confidence: 99%
See 2 more Smart Citations